Effect of platelet-rich plasma on skin flaps in rabbits - Aragón-Urrego, Catherine (2018)
Autologous platelet concentrates (APC) has been used as an accelerator of cutaneous healing in veterinary medicine. The aim of this study was to evaluate the effect of an APC on skin flaps in rabbits (Oryctolagus cuniculus). Ten New Zealand male rabbits were randomly divided into a control group and an APC group. A rotating cutaneous flap was made in the thoraco-dorsal region of the right thoracic limb of the rabbits. Half of the rabbits received APC infiltrated under the flap. Biopsies were taken from the union of the flap with the recipient bed at 3, 7, 14, and 21 days post-surgery. The histological analysis of the inflammatory infiltrate was made, and the proliferation of fibroblasts and type of collagen formed was determined. A significant difference was observed in the neutrophil count, macrophages and fibroblasts. The histological analysis showed that a single application of CAP does not reduce the healing time in skin flaps; however, it promotes the formation of blood vessels and reduces the inflammatory infiltrate in rabbits throughout experimental time.